2011
DOI: 10.1186/1475-2891-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetable supplementation in a controlled diet study alters the serum peptidome in a GSTM1-genotype dependent manner

Abstract: BackgroundCruciferous vegetable intake is inversely associated with the risk of several cancers. Isothiocyanates (ITC) are hypothesized to be the major bioactive constituents contributing to these cancer-preventive effects. The polymorphic glutathione-S-transferase (GST) gene family encodes several enzymes which catalyze ITC degradation in vivo.MethodsWe utilized high throughput proteomics methods to examine how human serum peptides (the "peptidome") change in response to cruciferous vegetable feeding in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Several examples of such genetic stratification are summraised in Table 1 [86][87][88][89][90]. A good example is provided by a recent proteomic trial, where interpretation of the protein patterns found was possible only when the results were stratified according to glutathione S-transferase mu 1 (GSTM1) genotypes [86].…”
Section: Proving Efficacy Of Broccoli In Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of such genetic stratification are summraised in Table 1 [86][87][88][89][90]. A good example is provided by a recent proteomic trial, where interpretation of the protein patterns found was possible only when the results were stratified according to glutathione S-transferase mu 1 (GSTM1) genotypes [86].…”
Section: Proving Efficacy Of Broccoli In Cancer Preventionmentioning
confidence: 99%
“…Several examples of such genetic stratification are summraised in Table 1 [86][87][88][89][90]. A good example is provided by a recent proteomic trial, where interpretation of the protein patterns found was possible only when the results were stratified according to glutathione S-transferase mu 1 (GSTM1) genotypes [86]. Steck and Hebert [107] summarised the literature showing an association between genotypic variation, measured as single nucleotide polymorphisms (SNPs), in glutathione S-transferase (GST) genes, and excretion of both dietary carcinogens and ITC metabolites after brassicaceous vegetable consumption.…”
Section: Proving Efficacy Of Broccoli In Cancer Preventionmentioning
confidence: 99%
“…An equal volume of 100 % acetonitrile was added to each serum sample to precipitate out large globular proteins as previously described [9, 10]. Samples were shaken for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we developed analytical methods using matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI–TOF MS) to identify changes in the serum peptidome [9, 10]. This type of spectrometry-based protein profiling has been used to identify novel diagnostic markers for disease [11, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Foods rich in b-carotene have been used in several studies to investigate how they could be used to alleviate vitamin A deficiency (van Jaarsveld et al, 2005;Low et al, 2007) and other carotenoids, such as lycopene, lutein, and zeaxanthin, to investigate effects on biomarkers of cardiovascular risk, DNA damage, inflammation, and macular degeneration (Chopra et al, 2000;Astley et al, 2004;Kopsell et al, 2006;Paterson et al, 2006;Beck et al, 2010). There have also been several human intervention studies with cruciferous vegetables to attempt to obtain experimental evidence to support epidemiological data for the health promoting effects of these vegetables (Kensler et al, 2005;Al Janobi et al, 2006;Gasper et al, 2007;Traka et al, 2008;Li et al, 2009;Navarro et al, 2009aNavarro et al, , 2009bYanaka et al, 2009;Brauer et al, 2011). Systematic reviews of human intervention studies that have involved both carotenoid-rich and glucosinolaterich foods, as have been done for flavonoid-rich foods (Hooper et al, 2008), would be timely.…”
Section: Human Intervention Studiesmentioning
confidence: 99%